Marking of meat productivity features in pairs of bGH, bGHR and bIGF-1 polymorphic genes in Aberdeen-Angus cattle - Dushayeva, L. Z.; Nametov, A. M.; Beishova, I. S.; Belaya, A.V.; Ulyanova, T. V.; Kovalchuk, A. M.; Tagirov, K. K.; Yuldashbayev, Y. A. (OnLine Journal of Biological Sciences . - 2021, 2021)
The purpose of the study is to identify paired combinations associated with meat productivity in Aberdeen-Angus cattle for the genes of the somatotropin cascade (growth hormone bGH, growth hormone receptor bGHR, insulin-like growth factor-1 bIGF-1). The determination of animal genotypes was carried out by PCR-RFLP. Results of statistical processing was carried out using the software capabilities of "Microsoft Excel 2010" and "Statistica 6.0". Paired combinations study of bGH, bGHR and bIGF-1 somatotropin cascade revealed marking diplotype polymorphic genes associated with signs of meat productivity and allowing for a comprehensive assessment of the Aberdeen-Angus cattle genetic potential in the postnatal development early stages. Thus, the animals’ live weight with the bGH-AluIVV-bIGF-1-SnaBIBB diplotype at the age of 24 months exceeds the Aberdeen-Angus breed live weight standard by 45 kg (12%) and the total sample-by 12.52 kg (3%). The bGH-AluILL-bIGF-1-SnaBIAA diplotype score is 2.93% higher than the total sample. The mass index average value of animals with the bGH-AluILV-bGHR-SspIFY diplotype at 18 months is 3.98% lower than the total sample. In animals with the bGHR-SspIFF-bIGF-1-SnaBIBB diplotype at the age of 24 months, the churn index value is lower than the total sample by 3.74%. Thus, the diplotypes bGH-AluIVV-bIGF-1-SnaBIBB and bGH-AluILL-bIGF-1-SnaBIAA can be considered genetic markers of increased meat productivity and the diplotypes bGH-AluILV-bGHR-SspIFY and bGHR-SspIFF-bIGF-1-SnaBIBB-reduced meat productivity. The animals’ selection with diplotypes that increase meat productivity will reduce the investment period and increase the agricultural production profitability. For breeding activities, it is recommended to maintain the animals’ number with the diplotypes bGH-AluIVV-bIGF-1-SnaBIBB and bGH-AluILL-bIGF-1-SnaBIAA. © 2021 Laura Zhanedilovna Dushayeva, Askar Myrzahmetovich Nametov, Indira Saltanovna Beishova, Alena Valentinovna Belaya, Tatyana Vladimirovna Ulyanova, Alexandr Mikhailovich Kovalchuk, Khamit Kharisovich Tagirov and Yusupzhan Artykovich Yuldashbayev. Цель исследования - выявить парные комбинации, связанные с мясной продуктивностью у абердинско-ангусского скота для генов соматотропинового каскада (гормон роста bGH, рецептор гормона роста bGHR, инсулиноподобный фактор роста-1 bIGF-1). Определение генотипов животных проводили методом ПЦР-ПДРФ. Результаты статистической обработки проводились с использованием программных возможностей «Microsoft Excel 2010» и «Statistica 6.0». Исследование парных комбинаций соматотропинового каскада bGH, bGHR и bIGF-1 выявило маркерные полиморфные гены диплотипов, связанные с признаками мясной продуктивности, и позволило провести комплексную оценку генетического потенциала абердин-ангусского скота на ранних стадиях постнатального развития. Так, живая масса животных с диплотипом bGH-AluIVV-bIGF-1-SnaBIBB в возрасте 24 месяцев превышает стандарт живой массы абердин-ангусской породы на 45 кг (12%), а по всей выборке - на 12,52 кг ( 3%).
Keywords: импакт-фактор 2021; скопус; scopus; научный журнал; периодическое издание; зарубежное издание; дальнее зарубежье; генотип животных; мясная продуктивность; абердинско-ангусская порода крс; живая масса скота